New Age with Chinese Characteristics? Translating Inner Child Emotion Pedagogies in Contemporary China. (June 2016) - Pritzker, Sonya E.
Abstract: This article examines the translation of inner child emotion pedagogies in contemporary China. With a focus on several interactions taking place within evening salons, the article observes the pedagogical strategies and metalinguistic practices that translate as well as transform inner child pedagogies in novel ways. I emphasize the ways in which these encounters play upon the boundaries between "inner" and "outer" selves in the teaching of a distinct discursive consciousness regarding the role of language and embodied expression in the healing of the inner self. I argue that this creates both a distillation as well as expansion of western psychotherapeutic ideologies of language, emotion, and the self. I further highlight the ways in which the interactions index a broadly distributed process of concurrent events and sociohistorical circumstances that bring adapted versions of psychotherapeutic and New Age spiritual discourse into China. This article argues that the translation of inner child emotion pedagogies in China unfolds through a process of living translation, in which specific encounters serve as instances in which the meaning and implications of semiotic and linguistic registers are continuously remade in an ongoing stream of embodied interactions that are mediated by various ideologies of language, emotion, and personhood. 本文探讨了在当代中国内在小孩情感教学法的翻译。通过"内在小孩疗愈晚间沙龙"的几次互动, 本文重点观察教学策略和元语言实践——即对内在小孩疗愈法的创新翻译和转化。在这种独特的话语意识教学中, 笔者强调, 冲突在"内在"和"外在"自我界限间作用的这种方式, 在治愈内在自我过程中, 对语言和形象化表达的作用。笔者认为, 这在语言、情感和自我方面同时凝练而拓展了的西方心理治疗体系。笔者进一步强调, 互动指向广泛分布的同期事件和社会历史状况的这种方式, 把本土化的心理治疗学和新世代心灵的语言带入了中国。本文认为, 在中国的内在小孩情感疗愈是通过当下翻译来展开的, 在此翻译过程中, 特定冲突被作为微观民族志的实例。这些例子中, 符号学和语言学记录的含义持续地通过语言、情感和人格知识体系在具象化的互动中获得。